Evaluate the quality of services provided by The Ministry of Education and schools and their implications for the educational process in government schools operating in the evening system for Syrians in Jordan from the teachers’ point of view: - Alnsoor, Eaman Hasan Mahmoud; Alnsoor, Amany Hasan Mahmoud; Al-Rahahleh, Rasha Mohammad Ali (Journal of Educational and Psychological Sciences, 2023)
This research aimed to evaluate the quality of services provided by the Ministry of Education and schools and their implications for the educational process in government schools operating in the evening system for Syrians in Jordan from the teachers’ point of view. To achieve the research objectives, a questionnaire was designed as a research tool. The descriptive approach was followed. The sample consisted of (151) teachers in public schools operating in the evening system for Syrians in Jordan. The research found that the services provided by the school to Jordanian students in government schools operating in the evening system for Syrians got a total average of (3.60 out of 5), at a (high) level. At the level of dimensions, the school administration came first; With an average of (3.93) and a high level, then the teaching method with an average of (3.19), and thirdly, the use of educational technology with an average of (3.04), both at a level (average), and finally the school environment with an average of (2.49) and at a level (weak), while the services provided by the Ministry of Education got a total average. (3.63 out of 5) any level (high). The research also found that there are statistically significant differences in the quality of services provided to Jordanian students from the school (method of teaching, school administration, school environment, use of educational technology), and for the quality of services provided to Jordanian students from the Ministry of Education (guiding and supervising) on the educational process in government schools operating in the evening system for Syrians in Jordan. Based on the results, the study recommended the necessity of ending the work of the two-shift system in government schools operating in the evening system for Syrian students in Jordan, and the need to impose an increase in the number of schools operating in the double-shift system.
Keywords: Assessment of the Quality of Educational Services; Syrian asylum; Public Schools; The Evening System